2017
DOI: 10.1038/npp.2017.175
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Protein Kinase C Signaling Mediates the Short-Term Memory Impairment Induced by Delta9-Tetrahydrocannabinol

Abstract: Cannabis affects cognitive performance through the activation of the endocannabinoid system, and the molecular mechanisms involved in this process are poorly understood. Using the novel object-recognition memory test in mice, we found that the main psychoactive component of cannabis, delta9-tetrahydrocannabinol (THC), alters short-term object-recognition memory specifically involving protein kinase C (PKC)-dependent signaling. Indeed, the systemic or intra-hippocampal pre-treatment with the PKC inhibitors prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 44 publications
2
28
0
1
Order By: Relevance
“…However, we did not find differences in the hippocampal neuroplasticity-associated parameters, including LTP induction and maintenance in the hippocampal Schaffer collateral-CA1 pathway, dendritic complexity of the hippocampal CA1 neurons, or changes in expression or phosphorylation levels of hippocampal neuroplasticity-related proteins between the CMI-168 and Chow mice. Among the selected neuroplasticity-related proteins, BDNF-TrkB signaling [17,18], CamKII [19], Erk1/2 [20], PKCζ [21], GluR1 [22], p38 [23], and GSK3 [24] have been linked to the learning and memory functions. SYT-1, SYT-4, and SNAP-25 are members of soluble N -ethylmaleimide-sensitive factor attachment protein receptor located in the presynaptic and postsynaptic regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not find differences in the hippocampal neuroplasticity-associated parameters, including LTP induction and maintenance in the hippocampal Schaffer collateral-CA1 pathway, dendritic complexity of the hippocampal CA1 neurons, or changes in expression or phosphorylation levels of hippocampal neuroplasticity-related proteins between the CMI-168 and Chow mice. Among the selected neuroplasticity-related proteins, BDNF-TrkB signaling [17,18], CamKII [19], Erk1/2 [20], PKCζ [21], GluR1 [22], p38 [23], and GSK3 [24] have been linked to the learning and memory functions. SYT-1, SYT-4, and SNAP-25 are members of soluble N -ethylmaleimide-sensitive factor attachment protein receptor located in the presynaptic and postsynaptic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Using these tasks, preclinical studies have indicated both acute and long-term effects of cannabinoid exposure. Acute THC has been demonstrated to affect object recognition memory in CD-1 mice (Barbieri et al, 2016; Busquets-Garcia et al, 2018), but not in other rodent strains (Ciccocioppo et al, 2002; Long et al, 2010; Swartzwelder et al, 2012; Kasten et al, 2017). It reliably produces anxiogenic and sedative effects at higher doses (Onaivi et al, 1990; Célérier et al, 2006; Schramm-Sapyta et al, 2007; Lee et al, 2015; Kasten et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…Of note, the A2AR/CB1R oligomer would likely result to be relevant for CBD capacity to mitigate the cognitive impairment induced by the psychoactive cannabis derivative  9 -THC in a declarative and spatial memory task. Although other brain areas contribute to the two-object recognition test performance, including perirhinal cortex and striatum [27,37], previous findings reveal a crucial role for hippocampus in the  9 -THC-induced memory impairment [30,31] suggesting this brain areas as the main target for this CBD modulation of A2AR-CB1R interaction. Interestingly, the pre-treatment with the preferentially pre-and post-synaptic A2AR antagonists SCH442416 and KW-6002, respectively [32], demonstrated for the first time that this CBD effect was mostly dependent on the activity of pre-synaptic A2AR receptors.…”
Section: Discussionmentioning
confidence: 94%
“…To this end, we first assessed the effects of  9 -THC in the two-object recognition test, which evaluates mainly hippocampal-and perirhinal cortex-dependent declarative memory performance [27]. Previous findings indicate that the hippocampus plays a crucial role in the CB1R agonists-induced memory impairment in the two-object recognition test evaluated both in an open field [28] or in a V-maze [29][30][31]. As expected,  9 -THC (3 mg/kg) induced a significant (P < 0.01, Table S1) reduction in the recognition index when administered immediately after training, which was reversed with a pretreatment with the selective CB1R antagonist SR141716A (1 mg/kg) (P < 0.05, Table S1) ( Fig.…”
Section: Cbd Blunts  9 -Thc-induced Cognitive Impairment But Not Lomentioning
confidence: 99%